THE INFLUENCE OF WORK DISCIPLINE AND CAREER DEVELOPMENT TO THE EMPLOYEE PERFORMANCE AT THE BPJS KETENAGAKERJAAN BRANCH OFFICE NORTH SULAWESI - Singal, Finny Suzana; Untu, Victoria (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Every organization,  whether private and governmental one, is oriented to long-term goals,  namely the  development of the organization and will try to improveits  performance in order to  achieve the vision and mission of the company. The purpose of this research was to determine influence of  employees’ discipline and career development to the employee performance at the BPJS Ketenagakerjaan branch office North Sulawesi. This research  used an associative method with the aim to see the relationship between variables. Data were analyzed using multiple linear regression and saturated sampling techniques is used to collect 35 sample employees. The results showed the discipline of work and career development, have a  significanly  simultaneous effect on the  employees performance. Labor discipline shows no significance,  whereas caeer development is significantly influence employce performance. Leaders BPJS Ketenagakerjaan north sulawesi branch offices, would have to put more attention to the employees’ discipline since it will affect the employees’ performance. Keywords: work discipline, career development and employee performance